Предмет: Алгебра, автор: Brawlstars585659575

Помогите пожалуйста!!!! ​

Приложения:

Ответы

Автор ответа: mursalovasuriya
1

Ответ:

 \frac{ {x}^{2}  - 36}{x + 3}  \times  \frac{1}{ {x}^{2}  + 6x}  -  \frac{x + 6}{ {x}^{2} - 3x }  =  \\  =  \frac{(x - 6)(x + 6)}{x + 3}  \times  \frac{1}{x(x + 6)}  -  \frac{x + 6}{x(x - 3)}  =  \\  =  \frac{x - 6}{x(x + 3)}  -  \frac{x + 6}{x(x - 3)}  =  \\  =  \frac{(x - 6)(x - 3) - (x + 6)(x + 3)}{x(x - 3)(x + 3)}  =  \\  =  \frac{ {x}^{2}  - 9x + 18 -  {x}^{2}  - 9x - 18}{x(x - 3)(x + 3)}  =  \\   =  \frac{ - 18x}{x( {x}^{2} - 9) }  =  -  \frac{18}{ {x}^{2} - 9 }

Похожие вопросы
Предмет: Математика, автор: Twinsister11